Rooted and renewing : imagining the Church's future in light of its New Testament origins - Troftgruben, Troy M., 1976- (Word & world books., 2019)
What does it mean to be church today? As changes in demographics, participation, and leadership continue to roil faith communities in the Western world, questions about the historic roots of church communities have become all the more important. Scholarly investigations of the historical texture of early Christian communities continue to advance our understanding, but are often too technical for non-experts for whom the questions may be more keenly felt. Troy M. Troftgruben provides an accessible, succinct survey of what we now know about the roots of Christian community, taking an "ancient-future" approach by engaging contemporary questions through classical sources. Rooted and Renewing turns to historical-critical and social-scientific studies to portray everyday realities in the earliest communities, especially the Pauline assemblies. Aimed at church members and leaders alike, the book encourages reflection on the church's past so as to explore how Christians are called to be the church in today's world